Edukasi Pasar Modal dan Pengenalan Security Crowdfunding sebagai Solusi Pendanaan UMKM Di Desa Cisantana - Amir Hamzah; Eiva Nurcahyani; Raka Suryana Talenta; Thifal Amatul Hadi; Nani Sumarni; Dina Nurochmah (CV. Armas Suan Sejahtera, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Cisantana Village, Kuningan Regency, still face limited understanding regarding investment in the capital market and funding through Security Crowdfunding mechanisms. This community engagement activity aimed to enhance the financial literacy of MSME players by providing direct education on the potential of capital market investment and alternative funding strategies using registered Security Crowdfunding platforms. The training methods included lectures, interactive discussions, and practical simulations to deliver an applied learning experience. A total of 51 MSME participants took part voluntarily from the local community. The effectiveness of the training was assessed through a comparison of pretest and posttest scores, which showed a significant improvement in comprehension. Additionally, participants responded positively, indicating that the training improved their knowledge and skills in making investment decisions and accessing alternative funding options. They also appreciated the presenters' mastery of both material and delivery techniques, which facilitated the understanding of complex concepts in a structured and accessible manner. This training is expected to contribute to the financial independence of MSMEs and broaden their access to safe and officially registered modern funding sources